Strength evaluation of oil palm stem trussed rafters - Jumaat, Mohd Zamin; Rahim, A.H.A.; Othman, J.; Midon, M.S. (Elsevier, 2006)
Research on the suitability of using oil palm stems as trussed rafters is reported in this paper. Previous studies indicated that certain portion of the stems had good potential to be used as structural components. Fink type trusses made from parts of oil palm stems were designed, fabricated and tested. Full-size load test was carried out since it was considered to be one of the most reliable methods of establishing the structural adequacy of roof trusses as well as their behaviors and modes of failure. The results obtained were compared to the results of hardwood timber trusses of similar configurations. The results indicate that oil palm stem has the potential to be exploited for use as roof trusses with some design modifications and proper grading of the oil palm stems.